KEHILANGAN HARA AKIBAT EROSI (Studi Kasus di Tegakan Jati) - B. Wisnu Didjajani (Agrovigor, 2012)
Teak Forest Management in Indonesia began at period of Governance of Dutch Colonialism in1860. After independence of Indonesia in 1945, teak forest was managed by Department of Forestry and now was managed by Perum Perhutani. During that time  have been applied by various approach of management which relate to sustainable principles, but with existence of ecosystem change, degradation of indication resource and productivity that teak forest was not managed to sustainable principles. On the other side, commerce of world wood claim the quality of wood coming from managed forest on sustainability principles. This research aim to studying erosion at various of trees age and nutrient loss. Result of research showed that increasing of crop age was degrade the erosion. Soil lose affects of erosion could bring consequence to losing of soil nutrition. Mean losing of soil nutrition per hectare at various teak plants age is : ( 13,8 - 74,3) kg of N; ( 8,7 - 36,2) kg of P; ( 7,2 - 35,2) kg of K; ( 54,6 - 219,2) kg of Ca and ( 7,2 - 28,2) kg of Mg.